PELATIHAN MODERNISASI PEMBELAJARAN BAGI GURU SMK DI BANDAR LAMPUNG - Suroto Suroto; Fanni Rahmawati; Rahmah Dianti Putri (Universitas Lampung, 2023)
Vocational High Schools (SMK), which have been the majority of schools producing unemployment, must immediately pay attention. The lack of optimal educational goals is also indicated because the teacher is less skilled in choosing and utilizing the facilities provided so that learning runs monotonously and is difficult for students to accept. Learning multimedia is one of the media that can be used by teachers so that learning goes well, is not monotonous, and can foster student learning motivation. Descriptive-explanative writing method with a qualitative approach, which aims to provide an understanding of the modernization of teacher learning in SMK. This service consists of several trainings and counseling which aim to provide understanding to teachers so that they have additional skills in choosing and making multimedia learning. With the skills possessed by the teacher, it is hoped that learning will be good, innovative and can get maximum results.Keywords: Multimedia, Skills, Teachers, Vocational High SchoolsDoi: https://dx.doi.org/10.23960/JPSI/v3i1.17-22